Drivers for international innovation activities in developed and emerging countries - Anja Schmiele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper aims to shed light on firm specific drivers that lead firms to internationalise their innovation activities. The paper draws a comprehensive picture of driving forces by including firm capabilities, characteristics of the firm’s competitive environment and the influence of innovation obstacles in the home country. In particular, the role of the potential driving forces is tested on the probability to carry out different innovative activities abroad (R&D, design/conception of new products, manufacturing of innovative products and implementation of new processes). In a second step these driving forces are used to observe their impact on the decision to locate innovation activities in various countries and regions (China, Eastern Europe, Western Europe and North America) as well as in groups of countries with similar levels of knowledge (country clubs). The analysis is based on the Mannheim Innovation Panel survey which represents the German CIS (Community Innovation Survey) contribution. Two survey waves are combined and result in a sample of about 1400 firms. The results show that the decision to perform innovation activities abroad is mainly driven by organisational capabilities such as absorptive capacities, international experience and existing technological competences of the respective firm. Innovation barriers at the German home base such as lack of labour and high innovation costs foster the set up of later-stage innovation activities abroad while the lack of demand demonstrates a barrier to the internationalisation decision for the development and manufacturing of new products. Location decisions receive the strongest influencing effects from the international experience of the firm. Firms which innovate in developing countries seem to require a more extensive level of international experience by international R&D cooperation.
Keywords: F23; L22; L25; O31; O32; O47; 330; Internationalisation of R&D; Innovation; Absorptive Capacities; Market Structure; China; Asia; Emerging countries; Innovation; Industrielle Forschung; Multinationales Unternehmen; Globalisierung; Auslandsproduktion; Deutsch; Marktstruktur; Deutschland; Schwellenländer; China; Asien; Osteuropa; Westeuropa; Nordamerika